An adaptive safety-risk mitigation plan at process-level for sustainable production in chemical industries: An integrated fuzzy-HAZOP-best-worst approach. (10th March 2022) - Nguyen, Hai-Tra; Safder, Usman; Kim, JeongIn; Heo, SungKu; Yoo, ChangKyoo
Abstract: Safety-risk management in the hydrocarbon processing industry necessitates the availability of appropriate data and decision-making tools. Operational factors may influence chemical and physical risk occurrences associated with high-hazard plant operation in the chemical process sectors. Thus, safety-risk technologies and assessments should be explored considering potential events that result in fatalities, property destruction, economic loss, and environmental degradation. This research established a systematic framework for reducing safety risks to decrease accidents and hazards associated with the inherent production processes, as well as proposing process-level maintenance techniques for the specified hydrocarbon processing industry. First, the hazards of chemical reactivity were studied to determine which equipment performance poses the greatest risk. Physical and chemical risks were obtained to configure out identical nodes of expressing severe hazard via a qualitative assessment using the HAZOP study. The fuzzy best-to-worst technique combined with an analytical network process (fuzzy-BWANP) was utilized to assess the safety-risk criticality due to the operational reaction process, environmental risk, economical safety, and occupational management. Furthermore, the annual loss of expectancy and exposure factors for the earlier categories based on their operational expenses and failure time were estimated. The case study examined how to increase the process feasibility of an acrylonitrile plant. Consideration of economic loss resulted in the extraction of a risk index that helps decision-makers in determining priority tasks for addressing urgent hazards in any hydrocarbon processing industry's safety management. Graphical abstract: Image 1 Research highlights: An integrated qualitative-quantitative safety-risk approach was developed. Twenty-nine risks factors in an acrylonitrile plant (AN) case were identified. Safety-risk analysis was investigated via chemical reactivity and physical damage. Pressure variation in scrubber was identified as the most crucial safety problem. Process disruption, S14, was got highest risk causality from fuzzy-BWANP approach.